THE MALAYSIAN PERSPECTIVE ON IMPOSING CIVIL LIABILITIES IN ROAD ACCIDENTS INVOLVING AUTONOMOUS VEHICLE (UUM Journal of Legal Studies, 2021)
The advancement of artificial intelligence (AI) technology has become the fundamental catalyst in the research and development of autonomous vehicle (AV). AVs equipped with AI are expected to perform better than humans and forecasted to reduce the number of road accidents. AV will improve humans’ quality of life, such as creating more mobility for the elderly and disabled, increasing productivity, and creating an environmentally friendly system. Despite AV’s promising abilities, reports indicate that AV can go phut, causing road fatalities to the AV user and other road users. The autonomous nature of AV exacerbates the difficulty in determining who is at fault. This article aims to examine the ability of the existing legal framework to identify the person at fault so as to determine the tortious liability in road accidents involving AV. This article demonstrated that the existing legal scheme is insufficient to determine tortious liability in road accidents involving AV. This article explored the possibility of shouldering the liability on the manufacturer, the user, and even on the AV itself. This article also investigated alternative approaches that could be adopted to resolve issues on the distribution of tortious liability in road accidents involving AV. The outcome of this article could contribute to issues relating to the liability of AI.